The history of the American Indians - Adair, James, approximately 1709-1783 (Book collections on Project MUSE., 2005)
James Adair was an Englishman who lived and traded among the southeastern Indians for more than 30 years, from 1735 to 1768. Adair's written work, first published in England in 1775, is considered one of the finest histories of the Native Americans.